Encapsulation of salmon peptides in marine liposomes: physico-chemical properties, antiradical activities and biocompatibility assays - Hanachi, Amine; Bianchi, Arnaud; Kahn, Cyril, J F; Velot, Emilie; Arab-Tehrany, Elmira; Cakir-Kiefer, Céline; Linder, Michel (Marine Drugs, 2022)
International audience Salmon byproducts (Salmo salar) generated by the food chain represent a source of long-chain polyunsaturated fatty acids (eicosapentaenoic acid (EPA): 20:5n-3; docosahexaenoic acid (DHA): 22:6n-3) and peptides that can be used as supplements in food for nutraceutical or health applications, such as in the prevention of certain pathologies (e.g., Alzheimer’s and cardiovascular diseases). The extraction of polar lipids naturally rich in PUFAs by enzymatic processes without organic solvent (controlled by pH-Stat method), coupled with the production of 1 kDa salmon peptides by membrane filtration, allowed the formulation of nanocarriers. The physicochemical properties of the nanoliposomes (size ranging from 120 to 140 nm, PDI of 0.27, zeta potential between −32 and −46 mV and encapsulation efficiency) were measured, and the bioactivity of salmon hydrolysate peptides was assessed (antioxidant and antiradical activity: ABTS, ORAC, DPPH; iron metal chelation). Salmon peptides exhibited good angiotensin-conversion-enzyme (ACE) inhibition activity, with an IC50 value of 413.43 ± 13.12 µg/mL. Cytotoxicity, metabolic activity and proliferation experiments demonstrated the harmlessness of the nanostructures in these experimental conditions.